"I'm not a jukebox where you push a button and then I sing": Negotiating Medicine Access in Physician–Patient Encounters. Issue 2 (15th December 2022) - Liu, Rui; Lundin, Susanne; Mirsalehi, Talieh; Troein, Margareta
Abstract : This article aims to deepen understandings of physician–patient encounters by investigating views and perceptions held by Swedish physicians and care seekers on medicine access. Through a relational approach and a focus on materialities of medicines as fluid and contingent, we conceptualize medicine access as situated everyday practices and physician–patient encounters as embedded in sociomaterial configurations. Through a bricolage approach, we present both quantitative and qualitative data from physicians and care seekers. We argue that diverging views on medicine access held by both parties do not necessarily position medical professional knowledge as opposed to lay knowledge. They are reflective of a shifting healthcare landscape and evolving expectations on provision and experiences of care services.